2003
DOI: 10.1007/bf02256432
|View full text |Cite
|
Sign up to set email alerts
|

Ciz1, Cip1 interacting zinc finger protein 1 binds the consensus DNA sequence ARYSR(0–2)YYAC

Abstract: The matrin 3 family of nuclear proteins consists of members with potentially diverse activities. Matrin 3 and NP220 share RNA-binding domains, and NP220 has been shown to recognize and bind to the DNA sequence, CCCCC (G/C). We have isolated and characterized another member of the matrin 3 family, designated NP94, from a medulloblastoma. This protein, also named Ciz1, has previously been characterized for its ability to interact with p21(Cip1/Waf1) and contains 3 zinc finger domains and a matrin 3-homologous do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 27 publications
3
59
1
Order By: Relevance
“…Recently, it was reported that human Ciz1 does not colocalise with newly synthesized DNA (Warder and Keherly, 2003), which might appear to contradict our own observations. However, there were differences in the way the two studies were conducted.…”
Section: Sub-cellular Distribution Of Ciz1contrasting
confidence: 99%
See 2 more Smart Citations
“…Recently, it was reported that human Ciz1 does not colocalise with newly synthesized DNA (Warder and Keherly, 2003), which might appear to contradict our own observations. However, there were differences in the way the two studies were conducted.…”
Section: Sub-cellular Distribution Of Ciz1contrasting
confidence: 99%
“…Ciz1 has been implicated in tumorigenesis (Warder and Keherly, 2003) and has been linked to the mammalian cell cycle machinery, both by its interaction with p21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which Ciz1 acts as a coactivator for ER is unclear at the moment. Because Ciz1 is known to interact with the DNA element (18) and because Ciz1 binds to the DNA-binding region of ER, we hypothesized that the DNA-binding activity of Ciz1 has an inherent role in ER-modifying activity. The DNA-binding motif of Ciz1 and its interaction with ER might create a better ER docking site on the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has previously been utilized to determine specific DNA-binding sites for Ciz1 (Warder and Keherly 2003), the MT domain of MLL (Ayton et al 2004), and RAP1 (Graham and Chambers 1994), for example. A 72-bp oligonucleotide was synthesized, comprising a randomized 30-bp central region flanked by known sequences.…”
Section: Selected and Amplified Binding Assay (Saab)mentioning
confidence: 99%